Formulasi dan Uji Aktifitas Antikutu Kepala (Pediculus humanus capitis) Sediaan Sampo Minyak Sereh Wangi (Citronella oil): Formulation and Test of Anti-Head Lice Activity (Pediculus humanus capitis) Citronella Oil Shampoo Preparation (Citronella oil) - nesa agistia; Nofriyanti Nofriyanti; Ratna Sari Dewi (LPPM Universitas Abdurrab, 2023)
One of the problems that reduce a person's confidence is pediculosis. Natural ingredients used as anti-lice are citronella oil (Citronella oil), citronella oil contains citronellal compounds. This study aims to obtain a shampoo preparation that has anti-head lice activity. Citronella oil is formulated in several concentrations, namely 5% (FI), 7.5% (FII) and 10% (FIII). Evaluation of shampoo preparations included organoleptic examination, pH, homogeneity, foam height, irritation, cleaning power, freeze and thaw and anti-lice activity. Data analysis used the One Way ANOVA statistical test to see the comparison formula against the time of tick death. Based on the evaluation of the preparations, it was found that the shampoo had a thick liquid consistency, white in color, had a distinctive smell of citronella oil and no phase separation, pH 5.62-5.69, homogeneous, good cleaning power test, non-irritating, stable, anti-lice activity test FI = 6.24 minutes, FII = 5.38 minutes, FIII = 3.68 minutes, there was a significant difference (p<0.05) between the formulas on the time of tick death.